Hydrogen Sulfide Sensitizes Acinetobacter baumannii to Killing by Antibiotics - Ng, Say Yong; Ong, Kai Xun; Surendran, Smitha Thamarath; Sinha, Ameya; Lai, Joey Jia Hui; Chen, Jacqueline; Liang, Jiaqi; Tay, Leona Kwan Sing; Cui, Liang; Loo, Hooi Linn; Ho, Peiying; Han, Jongyoon; et al. (Frontiers in Microbiology, 2020)
The production of endogenous hydrogen sulfide (H2S) has been shown to confer antibiotic tolerance in all bacteria studied to date. Therefore, this mediator has been speculated to be a universal defense mechanism against antibiotics in bacteria. This is assuming that all bacteria produce endogenous H2S. In this study, we established that the pathogenic bacteria Acinetobacter baumannii does not produce endogenous H2S, giving us the opportunity to test the effect of exogenous H2S on antibiotic tolerance in a bacterium that does not produce it. By using a H2S-releasing compound to modulate the sulfide content in A. baumannii, we demonstrated that instead of conferring antibiotic tolerance, exogenous H2S sensitized A. baumannii to multiple antibiotic classes, and was able to revert acquired resistance to gentamicin. Exogenous H2S triggered a perturbation of redox and energy homeostasis that translated into hypersensitivity to antibiotic killing. We propose that H2S could be used as an antibiotic-potentiator and resistance-reversion agent in bacteria that do not produce it.